2022
DOI: 10.3390/agriculture12010107
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Suaeda salsa/Zea mays L. Intercropping on Plant Growth and Soil Chemical Characteristics in Saline Soil

Abstract: Halophytes possess the capacity to uptake high levels of salt through physiological processes and their root architecture. Here, we investigated whether halophyte/non-halophyte intercropping in saline soil benefits plant growth and contains root-dialogue between interspecific species. Field and pot experiments were conducted to determine the plant biomasses and salt and nutrient distributions in three suaeda (Suaeda salsa)/maize (Zea mays L.) intercropping systems, set up by non-barrier, nylon-barrier, and pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…In this study, it was found that the intercropping suaeda/maize would produce the disadvantage of maize growth, which was consistent with the results of Wang et al (2022) [ 18 ]. This complex system was affected by uncertain factors, biotic as well as physical, that are essential for species development [ 27 , 28 , 29 , 30 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, it was found that the intercropping suaeda/maize would produce the disadvantage of maize growth, which was consistent with the results of Wang et al (2022) [ 18 ]. This complex system was affected by uncertain factors, biotic as well as physical, that are essential for species development [ 27 , 28 , 29 , 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…The nutrient relationship between two plants in the intercropping tends to be a mutual–competitive relationship. Wang et al (2022) found the soil nitrogen content to be reduced in the intercropping suaeda/maize, which suggested that the disadvantage of maize was caused by N competition [ 18 ]. In this study, N1 treatment could obviously promote the aboveground biomass of maize in the intercropping, not significantly different from that in the monoculture system ( Figure 1 ), which also indicated that there was nutrient competition between maize and suaeda.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a review paper, Panta et al (2014) (72) reported that some species of plants removed between 0.66 and 6.35 t ha -1 a -1 of NaCl. Halophytes have also been used as intercrops with watermelon (74), cotton (75), maize (76), and many other crops, as reviewed by (77). Until now, however, most of the studies on intercropping with halophytes have been done under greenhouse conditions, with both successful and unsuccessful responses (77).…”
Section: Roots and Soil Chemical Restoration Salinitymentioning
confidence: 99%